Agriculture information network of small and medium size vegetable farmers in Sri Lanka - Samarakoon, Samarakoon Mudiyansela Ajantha Kumara; Shamil, Mohamed Mihilar Mohamed (Univerzita Pardubice, 2010)
Article mainly pay attention; which types of information need, which types of information receive to them and weakness of pertaining vegetable information network. Sample of Kandy district vegetable famers selected to examine vegetable market network. According to findings there are many weakness are pertain present market information network. The survey indicates that there is a very high demand for information among vegetable farmers though information they receive doesn’t meet their information needs. Since, article has given suggestions to develop vegetable market information system in Sri Lanka.
Keywords: market information; small and medium size farmers; agriculture information; information channels; information needs